Characterization and Screening of Thermophilic Bacillus Strains for Developing Plant Growth Promoting Consortium From Hot Spring of Leh and Ladakh Region of India - Verma, Jay Prakash; Jaiswal, Durgesh Kumar; Krishna, Ram; Prakash, Satya; Yadav, Janardan; Singh, Vijai (Frontiers in Microbiology, 2018)
In the present investigation, the main aim is to identify and characterize the potential drought tolerant plant growth promoting consortium for agricultural productivity. Three bacterial isolates were isolated from hot spring of Chumathang area of Leh district. Bacillus species (BHUJP-H1, BHUJP-H2 and BHUJP-H3) were done some biochemical tests including catalase, cellulase, amylase, indole-3-acetic acid, phosphate solubilisation, production of ammonia, siderophore and hydrogen cyanide. Molecular characterization of isolates was done by 16 S rDNA sequencing e.g. Bacillus subtilis BHUJP-H1 (KU312403), Bacillus sp. BHUJP-H2 (KU312404) and Bacillus licheniformis BHUJP-H3 (KU312405). The genetic diversity of the isolates was assessed by seven inter simple sequence repeat, all primer shows high polymorphism. The highest polymorphism efficiency and polymorphism information content showed by UBC-809 and UBC-836 which were 100% and 0.44 respectively, the lowest is by UBC-807 75% and 0.28 respectively. On an average 90.69% polymorphism efficiency and 0.40 polymorphism information contents obtained by used markers. The highest, 11.08 and the lowest, 4.50 effective multiplex ratios obtained for primer UBC-823 and UBC-807, on an average 7.99 effective multiplex ratio obtained. The highest, 4.89 and the lowest, 1.25 marker indexes obtained by UBC-836 and UBC-807 respectively and on an average 3.24 obtained. The UPGMA cluster analysis divided a population into two clusters I and II, in which BHUJP-H1 and BHUJP-H2 grouped under same while BHUJP-H3 grouped under another cluster. The treatment combination of Bacillus subtilis BHUJP-H1, Bacillus subtilisBHUJP-H1+ Bacillus licheniformis BHUJP-H3 and Bacillus subtilis BHUJP-H1+ Bacillus sp. BHUJP-H2+ Bacillus licheniformis BHUJP-H3 were recorded better combination for enhancing plant growth attributes of Vigna radiata as compared to control and others. The plant growth promoting consortium e.g. Bacillus subtilis BHUJP-H1, Bacillus subtilis BHUJP-H1+Bacillus licheniformisBHUJP-H3 and Bacillus subtilisBHUJP-H1+ Bacillussp. BHUJP-H2+ Bacillus licheniformis BHUJP-H3 can be further used as effective microbial inoculant for enhancing the production of mungbean in field conditions. Bacillus sp. BHUJP-H1 and Bacillus sp. BHUJP-H2 may use as drought tolerant plant growth promoting consortium for enhancing the sustainable agricultural productivity.